The Influence Of Brand Awareness, Call To Action, And Customer Reviews On Purchase Decisions Of Taboya Skincare Products On Tiktok Shop - Ghishela Yuwanasari; Muhammad Gunawan Wibisono; Parwita Setya Wardhani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
TikTok Shop is an e-commerce feature integrated within the TikTok application that allows users to buy and sell products without leaving the platform. This feature utilizes the power of short, interactive, and entertaining videos to promote products directly to the audience. This study aims to analyze the influence of brand awareness, call to action, and customer reviews on purchase decisions for Taboya Skincare products on TikTok Shop, both partially and simultaneously. This research employs a quantitative method, with data collected through questionnaires distributed to 100 Taboya Skincare buyers in Surabaya. Data analysis was conducted using multiple linear regression, with the F-test and t-test used as hypothesis testing tools. The results indicate that brand awareness, call to action, and customer reviews have a significant influence on purchase decisions on TikTok Shop, both partially and simultaneously, with an F-test significance value of 0.000 (< 0.05).